LANDSCAPE IN THE WORKS OF ALISHER NAVOI - Toshpulatova Maftuna Yodgorjon kizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the ideological and artistic functions, role, and significance of the depiction of nature, that is, landscape, in the works of the great thinker Hazrat Mir Alisher Navoi. In the poet’s epic poems of the Khamsa and his lyrical heritage, nature is examined not only as the setting in which events take place, but also as an element closely connected with the human psyche, expressed through symbolic images and artistic devices.